Effects of Induced Stress on Seismic Waves: Validation Based on Ab Initio Calculations. Issue 1 (23rd January 2019) - Tromp, Jeroen; Marcondes, Michel L.; Wentzcovitch, Renata M. M.; Trampert, Jeannot
Abstract: When a continuum is subjected to an induced stress, the equations that govern seismic wave propagation are modified in two ways. First, the equation of conservation of linear momentum gains terms related to the induced deviatoric stress, and, second, the elastic constitutive relationship acquires terms linear in the induced stress. This continuum mechanics theory makes testable predictions with regard to stress‐induced changes in the elastic tensor. Specifically, it predicts that induced compression linearly affects the prestressed moduli with a slope determined by their local adiabatic pressure derivatives and that induced deviatoric stress produces anisotropic compressional and shear wave speeds. In this article we successfully compare such predictions against ab initio mineral physics calculations for NaCl and MgO. Key Points: We compare ab initio calculations of effects of induced stress on elastic parameters with predictions based on a continuum mechanics theory We find that the two methods are in good agreement, without the need of higher‐order theories of elasticity The theory currently in use for accommodating the effects on nonhydrostatic prestress on seismic wave propagation needs to be modified